2023
DOI: 10.3390/ma16062528
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Milled Municipal Solid Waste Incineration Bottom Ash on Cement Hydration and Mortar Properties

Abstract: Large amounts of municipal solid waste incineration bottom ash (MSWI BA) are formed worldwide, and this quantity is growing because of the establishment of new waste-to-energy plants. This waste is generally kept in landfills but can be used for the manufacturing of cementitious building materials. This article analyzes the use of MSWI BA as a microfiller in cement mortars. The effects of MSWI BA on the properties of cement binder and mortar were analyzed by using them separately or in combination with other m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…MSWIBA is characterized by an unstable source, complex composition, nonuniform particle size distribution, and low reactivity, so it is necessary to adopt an activation treatment method to address the difficulties and problems of MSWIBA in engineering utilization [13]. Numerous scholars have explored the effect of MSWIBA at different blending levels on cement mortar or cement and found that bottom slag reduces the slump value [5,[13][14][15][16][17][18][19][20][21]. In contrast, the opposite trend was observed when used as a cement substitute.…”
Section: Introductionmentioning
confidence: 99%
“…MSWIBA is characterized by an unstable source, complex composition, nonuniform particle size distribution, and low reactivity, so it is necessary to adopt an activation treatment method to address the difficulties and problems of MSWIBA in engineering utilization [13]. Numerous scholars have explored the effect of MSWIBA at different blending levels on cement mortar or cement and found that bottom slag reduces the slump value [5,[13][14][15][16][17][18][19][20][21]. In contrast, the opposite trend was observed when used as a cement substitute.…”
Section: Introductionmentioning
confidence: 99%